Bad‐Metal‐Layered Sulfide Oxide CsV2S2O. Issue 1 (9th December 2015) - Valldor, Martin; Merz, Patrick; Prots, Yurii; Schnelle, Walter
Abstract: Through a solid‐state reaction between stoichiometric amounts of a mixed cesium oxide Cs2 O1.3, VS, S, and V2 O5, a polycrystalline powder of CsV2 S2 O was obtained. Small single crystals could be grown in a CsCl melt by allowing Cs2 SO4, V metal and S powders to react. The crystals have a plate‐like morphology, consistent with the tetragonal crystal‐structure symmetry [ P 4/ mmm, a = 3.9455(1), c = 7.4785(1) Å]. Magnetic measurements suggest that CsV2 S2 O is a temperature‐independent paramagnet, and resistivity data concur with a bad metal. The mixed oxidation state of V on one crystallographic site offers a tentative explanation of the electronic properties of the title compound. Abstract : CsV2 S2 O has a tetragonal crystal structure and contains Cs‐separated V‐S‐O layers with relatively short V–V distances of 2.790 Å. V has formally a charge of +2.5, resulting in temperature‐independent paramagnetism and bad‐metal‐like electric conductivity.